Analysis of food consumption status, body weight change and body composition ın ındividuals with substance use disorders: a systematic - Urhan, Murat; Ergün, Can; Gezmen Karadağ, Makbule (Progress in Nutrition, 2018)
This is a systematic literature review. The review aimed to examine the nutritional habits and status of individuals   with a substance use disorder during their substance use and during treatment for substance use. The literature review was conducted using the databases Medline, Cochrane Library, Ovid, and Science Direct with   no limitations as to dates. The researcher used the combinations of the keywords “substance abuse, substance addiction, illicit drugs, nutrition, diet, weight loss, weight gain, dietary patterns, malnutrition, anthropometry” to do the searching. Using these keywords, the search   provided access to 86 studies.  Twenty-seven of these studies fit the criteria and were taken under examination. The data produced by this examination demonstrated that the individuals that suffered from substance use disorder had poor dietary habits, and as a result, they had a range of nutritional problems, from malnutrition to obesity. These individuals commonly skipped meals, and mainly preferred high-fat foods as well as sugar and food containing sugar.  The treatment process also has its unique problems, and crucial increases in body weight were observed during this period.